(untitled) (Eurasian Research Bulletin, 2023)
The article effectively teaches self-preparation of goals and objectives, preparation of geographical specialties, professional recruitment, staff training, preparation, preparation for self-study, preparation, preparation for self-study, preparation, preparation for independent decision-making.during the meeting, issues related to compliance with the training regime, increasing the importance of training and professional development of education specialists were discussed